Restoration of the Petite Maison, Corseaux, 1924, Le Corbusier and Pierre Jeanneret. Construction Practice as Research - Graf, Franz; Marino, Giulia (Docomomo Journal, 2015)
The Petite Maison, or the villa Le Lac was built by Le Corbusier and Pierre Jeanneret at Corseaux, near Vevey, in 1924 for the parents of the former. Various modifications were made from then until 1973. The exteriors, façades, gardens and enclosures of this emblematic work were repaired and restored based on detailed research of the fabric and a well judged program of conservation which concluded in June 2015. This essay reports on some of the specifics of the project, the construction itself, the problems of ageing that the architects had to address, and the most recent conservation works (2013–15).